การพัฒนามอดูลดาลีสำหรับระบบส่องสว่างของหลอดฟลูออเรสเซนต์ - รวิชญ์ ธีรวิโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This thesis presents the development of a lighting control system for fluorescent lamps based on DALI protocol.The developed system consists of 3 main parts, i.e. Zigbee coordinator module, master module and slave module.The Zigbee coordinator module functions as an agent for receiving the user commands and sending these commands to the master module through Zigbee/IEEE 802.15.4 protocol standard.Upon receiving the commands from Zigbee coordinator module, the master module sends them to control the slave module by using DALI protocol in communication.The controlling functions of Zigbee coordinator module and master module are implemented by dsPIC33FJ256GP506 microcontrollers, while the slave module uses the PIC18F67J60 microcontroller. A Graphic User Interface program is also developed to ease issuing DALI commands such as light control, parameter setting and etc. Moreover, the developed system supports a saving energy mode which can automatically adjust light intensity level in the room as well as automatically turning on and off the light depending on the human presence in the room.